Wilson′s disease: A study of 21 cases from north-west India - Panagariya Ashok; Sureka Rajender; Sharma Anjani; Dev Amit; Agarwal Neeraj (Annals of Indian Academy of Neurology, 2007)
Wilson′s disease is an inborn error of copper metabolism, which is potentially treatable. This prospective study reports 21 cases of Wilson′s disease from north-west India having various clinical, biochemical and radiological features. The study highlights that the juvenile forms showed predominantly dystonic features with high frequency of seizures, while elderly group of patients showed predominantly cerebellar features. The absence of family history and relative lack of previous hepatic involvement may lead to the delay in diagnosis.